2001
DOI: 10.1177/03635465010290041801
|View full text |Cite
|
Sign up to set email alerts
|

Superior Labral Strain during the Throwing Motion

Abstract: We studied the strain on the superior labrum of 10 fresh-frozen cadaveric shoulders with the arm in simulated positions of a pitching motion. We used linear transducers to measure the strain in both the anterior and posterior superior labrum with the arm in various planes and rotations simulating the motions of pitching: early cocking, late cocking, acceleration, deceleration, and follow-through. Predetermined loads, according to the percent of maximum voluntary contraction of the biceps muscle during each pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 30 publications
(44 reference statements)
5
34
2
Order By: Relevance
“…Many investigators suspect that this lesion may develop through traction on the long head of the biceps. 1,3,5,12,13,20,25,26,30,32 This traction on the biceps likely has an active component (muscle firing) 26,32 and passive component (positioning) 3,5,13 that contribute to the pathogenesis of SLAP lesions.Several physical examination tests have been described for diagnosing SLAP lesions. 2,7,9,10,14,18,21,[28][29][30][31] They can be classified into 2 general categories: those that place a tensile force on the biceps tendon and those that compress the labrum between the humeral head and glenoid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigators suspect that this lesion may develop through traction on the long head of the biceps. 1,3,5,12,13,20,25,26,30,32 This traction on the biceps likely has an active component (muscle firing) 26,32 and passive component (positioning) 3,5,13 that contribute to the pathogenesis of SLAP lesions.Several physical examination tests have been described for diagnosing SLAP lesions. 2,7,9,10,14,18,21,[28][29][30][31] They can be classified into 2 general categories: those that place a tensile force on the biceps tendon and those that compress the labrum between the humeral head and glenoid.…”
mentioning
confidence: 99%
“…Many investigators suspect that this lesion may develop through traction on the long head of the biceps. 1,3,5,12,13,20,25,26,30,32 This traction on the biceps likely has an active component (muscle firing) 26,32 and passive component (positioning) 3,5,13 that contribute to the pathogenesis of SLAP lesions.…”
mentioning
confidence: 99%
“…They suggest that when the shoulder is placed in a position of abduction and maximal external rotation (ER), the rotation produces a twist at the base of the biceps, transmitting torsional force to the anchor (Figure 2). Pradham et al 41 recently measured superior labral strain in a cadaveric model during each phase of the throwing motion. They noted that increased superior labral strain occurred during the late cocking phase of throwing.…”
Section: Pathomechanics Of Slap Lesionsmentioning
confidence: 99%
“…Strains in the superior labrum have been investigated under conditions that are experienced during throwing. 30,34 In these laboratory studies, labral strains were measured using differential variable reluctance transducers (DVRTs) that were affixed to the superior labrum at the anterior and posterior attachments of the LHB tendon.…”
Section: Introductionmentioning
confidence: 99%
“…Pradhan et al 30 found that the posterosuperior labrum experience significantly greater strains than the anterosuperior labrum. Rizio et al used a similar experimental model to Pradhan et al but induced instability by creating a labral lesion.…”
Section: Introductionmentioning
confidence: 99%